The transcriptional landscape of Shh medulloblastoma - Skowron, Patryk; Farooq, Hamza; Cavalli, Florence M G; Morrissy, A Sorana; Ly, Michelle; Hendrikse, Liam D; Wang, Evan Y; Djambazian, Haig; Zhu, Helen; Mungall, Karen L; Trinh, Quang M; Zheng, Tina; et al. (Nature communications, 2021)
Sonic hedgehog medulloblastoma encompasses a clinically and molecularly diverse group of cancers of the developing central nervous system. Here, we use unbiased sequencing of the transcriptome across a large cohort of 250 tumors to reveal differences among molecular subtypes of the disease, and demonstrate the previously unappreciated importance of non-coding RNA transcripts. We identify alterations within the cAMP dependent pathway (GNAS, PRKAR1A) which converge on GLI2 activity and show that 18% of tumors have a genetic event that directly targets the abundance and/or stability of MYCN. Furthermore, we discover an extensive network of fusions in focally amplified regions encompassing GLI2, and several loss-of-function fusions in tumor suppressor genes PTCH1, SUFU and NCOR1. Molecular convergence on a subset of genes by nucleotide variants, copy number aberrations, and gene fusions highlight the key roles of specific pathways in the pathogenesis of Sonic hedgehog medulloblastoma and open up opportunities for therapeutic intervention.
Keywords: Young Adult; Gene Expression Regulation, Neoplastic; Hedgehog Proteins; transkriptom; Male; Child, Preschool; Middle Aged; genetická variace; mladý dospělý; Adolescent; Infant; Child; Gene Regulatory Networks; regulace genové exprese u nádorů; signální transdukce; Transcriptome; dítě; Adult; dospělí; mužské pohlaví; Cerebellar Neoplasms; meduloblastom; Signal Transduction; mladiství; předškolní dítě; genové regulační sítě; lidé; ženské pohlaví; proteiny hedgehog; Humans; kojenec; Genetic Variation; Female; lidé středního věku; nádory mozečku; Medulloblastoma